Metastasis-associated lung adenocarcinoma transcript 1 as a common molecular driver in the pathogenesis of nonalcoholic steatohepatitis and chronic immune-mediated liver damage - Sookoian, Silvia Cristina (2018)
Long noncoding RNAs (lncRNAs) are functional molecules that orchestrate gene expression. To identify lncRNAs involved in nonalcoholic fatty liver disease (NAFLD) severity, we performed a multiscale study that included: (a) systems biology modeling that indicated metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) as a candidate lncRNA for exploring disease-related associations, (b) translational exploration in the clinical setting, and (c) mechanistic modeling. MALAT1 liver profiling was performed in three consecutive phases, including an exploratory stage (liver samples from patients with NAFLD who were morbidly obese [n = 47] and from 13 individuals with normal liver histology); a replication stage (patients with NAFLD and metabolic syndrome [n =49]); and a hypothesis-driven stage (patients with chronic hepatitis C and autoimmune liver diseases, [n = 65]). Liver abundance of MALAT1 was associated with NAFLD severity (P = 1 × 10-6); MALAT1 expression levels were up-regulated 1.75-fold (P = 0.029) and 3.6-fold (P = 0.012) in patients with nonalcoholic steatohepatitis compared to those diagnosed with simple steatosis (discovery and replication set, respectively; analysis of covariance adjusted by age, homeostasis model assessment, and body mass index). Quantification of liver vascular endothelial growth factor A messenger RNA, a target of MALAT1, revealed a significant correlation between the two RNAs (R, 0.58; P = 5 × 10-8). Increased levels of MALAT1 were also associated with autoimmune liver diseases. Interactome assessment uncovered significant biological pathways, including Janus kinase-signal transducers and activators of transcription and response to interferon-γ. Conclusion: Deregulated expression of MALAT1 stratifies patients into the histologic phenotypes associated with NAFLD severity. MALAT1 up-regulation seems to be a common molecular mechanism in immune-mediated chronic inflammatory liver damage. This suggests that convergent pathophenotypes (inflammation and fibrosis) share similar molecular mediators.